DEVELOPMENT OF MULTIPLICATION BOARD MEDIA (PAPER) TO IMPROVE THE MULTIPLICATION SKILLS OF 2ND-GRADE ELEMENTARY SCHOOL STUDENTS - Uswah, Fadhilah; Siregar, Lailatun Nur Kamalia (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
Mathematics is a subject that develops thinking and problem solving abilities which have a very important role in students' daily lives. Mathematical objects are abstract so media is needed to explain this. One of the media that can be used is the Multiplication Board (PaPer) media. This research aims to develop and test the effectiveness of this media in improving students' multiplication abilities in class II. The method used is RnD (Research and Development) using the ADDIE (Analysis, Design, Development, Implementation and Evaluation) model. Data collection techniques use observation techniques, test interviews and teacher and student questionnaires. Data analysis was carried out using qualitative data from observations and interviews. And quantitative data based on pretest-posttest results. The product developed was then tested for the suitability of the multiplication board media which was assessed by media experts with a score of 92% and material experts with a score of 93.7%. placing it in the category of very valid or very suitable for use. The increase in students' multiplication skills can be seen from the pretest score of 49% and post-test score of 90.9%. Thus, this multiplication board media is considered relevant and suitable for use in this research. Apart from that, positive responses were obtained from teachers with scores 96% and from students with average scores 97,1% effective in improving students' multiplication abilities